Analisis Efisiensi Operasional Dan Keputusan Investasi Terhadap Keunggulan Bersaing Dengan Intellectual Capital Sebagai Variabel Pemoderasi Di Rumah Sakit Umum Daerah Tarakan - Bastian, Hendra; Husnatarina, Fitria; Priyati, Rini Yayuk (SEIKO : Journal of Management & Business, 2024)
The purpose of this study is to analyze the effect of operational efficiency and investment decisions on competitive advantage the effect of intellectual capital in moderating between operational efficiency and investment decisions on competitive advantage at Tarakan Regional General Hospital. The population in this study are 744 employees of Tarakan Regional General Hospital with the sample of 260 employees. The analysis technique used in this study is a linear regression analysis using moderation regression analysis. The results of the study are as follows. First, operational efficiency has a positive and significant effect on competitive advantage. Second, investment decisions have a positive and significant effect on competitive advantage. Third, intellectual capital can moderate and strengthen the relationship between operational efficiency and competitive advantage. Lastly, intellectual capital can moderate and strengthen the relationship between investment decisions and competitive advantage at Tarakan Regional General Hospital. Keywords: Operational efficiency, investment decisions, competitive advantage, intellectual capital